2006
DOI: 10.1136/jnnp.2005.080390
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and MRI features of Japanese patients with multiple sclerosis positive for NMO-IgG

Abstract: This study investigates the relation between the serological status of NMO (neuromyelitis optica)-IgG and the clinical and MRI features in Japanese patients with multiple sclerosis. Serum NMO-IgG was tested in 35 Japanese patients diagnosed with multiple sclerosis, including 19 with the optic-spinal form of multiple sclerosis (OSMS), three with the spinal form of multiple sclerosis (SMS), and 13 with the conventional form of multiple sclerosis (CMS), which affects the brain. NMO-IgG was detected in 14 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
172
5
12

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(210 citation statements)
references
References 13 publications
21
172
5
12
Order By: Relevance
“…In our series, among clinically defined NMO patients, NMO-IgG was positive in 64.3%. This seroprevalence is similar to that observed by others 3,8 .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In our series, among clinically defined NMO patients, NMO-IgG was positive in 64.3%. This seroprevalence is similar to that observed by others 3,8 .…”
Section: Discussionsupporting
confidence: 79%
“…In that seminal paper the authors found sensitivity and specificity for NMO diagnosis of 73% and 91%, respectively 3 . In Japan, authors detected NMOIgG in more than half of OSMS patients (63% sensitivity) 8 , suggesting that NMO and OSMS could be the same entity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A radiological feature of NMO is a longitudinally extensive cord lesion, often extending over three or more spinal segments, but MS involves fewer than two spinal segments. 7,8 In our Patient MRI of cervical and thoracic spine revealed a longitudinal area of hyperintensity and spinal cord thickening from C3-T1 in T2-weighted image which is consistent with the radiographic diagnostic criteria for NMO.…”
Section: Discussionmentioning
confidence: 53%
“…In a French study, Marignier and colleagues reported that there was no difference between NMOIgG sero-positive and sero-negative NMO patients according to their clinical, CSF, and imaging features 14 . However, in the Japanese, AQP4 antibody-positive NMO/OSMS patients had a greater frequency of longitudinally extensive spinal cord or brain lesions than did anti-AQP4 antibody-negative NMO/OSMS patients 9,[15][16][17] . These discrepancies may be accounted for by patient selection (NMO versus OSMS patients; different populations) and false-negative findings because of the low sensitivity of the assay.…”
Section: Discussionmentioning
confidence: 99%